2013
DOI: 10.1007/s12134-013-0294-4
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Local Swedish Refugee Policy

Abstract: In the Swedish migration system, the local level plays a crucial role since the municipalities have full autonomy to accept or decline refugees. This has created a considerable variation in numbers of immigrants among municipalities, and there is a large variation in local societies' willingness to receive refugees. In this study, we focus on all the Swedish municipalities for a time span of several years and derive from economic, demographic, socio-cultural, and explanatory factors that have been put forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Related to economic circumstances is the demographic situation. In relation to theories of a demand for additional labour (Piore ) and incentives for increasing the population in the municipality, we argue, in accordance with empirical proof from previous Swedish research (Lidén & Nyhlén ), that smaller municipalities are more inclined to receive refugees. We therefore add an indicator measuring population size.…”
Section: Methods and Datasupporting
confidence: 88%
See 3 more Smart Citations
“…Related to economic circumstances is the demographic situation. In relation to theories of a demand for additional labour (Piore ) and incentives for increasing the population in the municipality, we argue, in accordance with empirical proof from previous Swedish research (Lidén & Nyhlén ), that smaller municipalities are more inclined to receive refugees. We therefore add an indicator measuring population size.…”
Section: Methods and Datasupporting
confidence: 88%
“…While we can only speculate about the causes for this relationship, it might be that it serves as a proxy for other properties that causes municipalities to initiate a reception (cf. Lidén & Nyhlén ). Furthermore, income distribution, measured as a Gini coefficient, yields a positive influence.…”
Section: Empirical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Decentralized welfare states, like the Scandinavian countries, settle and enrol refugees in tailor‐made, multi‐year integration programmes, implemented at the local government level (Valenta and Bunar ; OECD , 11). Studies in Sweden and Norway have shown that local skepticism to receiving refugees is reduced by municipal affluence and by framing the issue as an administrative one rather than a political one (Liden and Nyhlen , ; Steen ). Other studies of Scandinavian refugee settlement policies have focused differences in local responses to state ambitions in liberal Sweden and restrictive Denmark (Myrberg ).…”
Section: Introductionmentioning
confidence: 99%